Development of Tourism in the Danube Tourist Region of Bulgaria (Geography and Tourism, 2014)
The Danube tourist region of Bulgaria consists of the Bulgarian section of the Danube River, adjoining islands, and territories south of the river. It is one of the newly-formed Bulgarian tourist regions. The aim of this article is to characterize tourist functions of the comparatively badly-studied Bulgarian section of the Danube River and the Danube tourist region. In order to achieve the aim, the article considers the following problems: territorial definition, tourist and resource potential check; characterization of the contemporary development of tourism; problems and prospects for its future progress.